Psychological consulting service to athletes in challenging life situations - Polyakov, E. A.; Kislyakov, P. A.; Senkevich, L. V.; Bychkova, L. A. (Theory and Practice of Physical Culture, 2017)
Every initiative to improve competitive success rates and secure persistent progress implies due psychological consulting service being provided to the athletes facing a variety of sport-specific and life problems. The study was designed to find the psychological consulting service methods most efficient in application to athletes. It gives descriptions of four efficient psychological consulting service methods applicable to athletes exposed to stresses due to professionalization challenges in sports (by Occasional Fellow Traveller method), or post-traumatic stresses (by Structured Confession method), or facing sport-motivation related problems (by Rational Emotive Behaviour Therapy), or problems due to inadequate thinking and acting culture (by Life Skills Developing service). The article gives a few cases of practical consulting services, with a special emphasis on the benefits of the reported consulting tools in application to young athletes and coaches (under 30 years of age) facing some life problems; with the service benefits being verified by the psychological/ psychosomatic state improvements; increased sport motivations; due understanding of the origins of the difficulties; and successful solutions of the problems faced in the sport-specific domain and other life situations. The practical methodologies outlined in the article may be helpful for the sport psychologists seeking, in cooperation with the coaches, to improve the competitive success rates and secure persistent progress of young athletes.